IMPLEMENTASI PROGRAM ESTRAKURIKULER OLAHRAGA O2SN UNTUK MENUMBUHKAN MINAT DAN BAKAT PESERTA DIDIK SEJAK DINI - Elsa Sefrina; Gupo Matvayodha; Ilyas Idris (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe the implementation of the O2SN extracurricular sports program in fostering students' interests and talents from an early age at SDN 073/IX Simpang Sungai Duren, as well as identifying supporting factors, inhibiting factors, and teacher innovations in its implementation. This study uses a qualitative approach with a descriptive research type. The research subjects include sports teachers, principals, and students who participate in extracurricular sports activities. Data collection techniques are carried out through observation, in-depth interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the O2SN extracurricular sports program is implemented in a planned manner through the preparation of training schedules, selection of sports branches according to student interests, and tiered coaching from lower to higher classes. The implementation of the program is able to increase students' interests, talents, discipline, self-confidence, teamwork, and basic sports technical abilities. The main supporting factors include school support, the active role of coaching teachers, and student enthusiasm, while the inhibiting factors are limited sports facilities and infrastructure. The novelty of this research lies in the disclosure of teachers' strategies and innovations in optimizing the development of extracurricular sports O2SN through the use of limited facilities and tiered development to foster students' interests and talents from an early age.